MENCIPTAKAN SDM SEBAGAI "HUMAN CAPITAL" MELALUI BUDAYA ORGANISASI - Johny Rusdiyanto (Journal of Management and Business, 2004)
In the future, the existence of organizations will very depends on its' capabilities to cover and handle the unpredictable changes of environment around the world. As Chatell said, "All organizations should be have three ultimate capabilities that enable organizations to become more responsive, adaptive and innovative”. Are organizations today prepares to fight for the future in uncontrollable conditions? The answer of this question is depends on theirs' Human resources availability within organizations. Organization will become more innovated when they have Human Resources with innovation competencies to create the best performance. Stewart say, this specialized Human resource be known as a "Human Capital”. They work not just as a worker” but more to act as a "thinker Some efforts to create employee to become a human capital find highly success when management of its organization give highly support through organization culture building to match theirs' expectation to create employee as a human capital. This article explains deeply about the role of organization culture and its ’ contribution to support the making of a human capital in an organization.